Strategi Pemasaran dalam Meningkatkan Pendapatan Es Coklat Berdua di Kota Bukittinggi - Aisya, Lativa; Putra, Indika Juang (Lembaga Yasin AlSys, 2026)
Marketing strategies in the microenterprise sector, particularly contemporary beverage businesses, have received attention in various studies, but research that specifically integrates the 4P marketing mix, SWOT analysis, and the perspective of sharia marketing in increasing business income remains limited. This study aims to analyze the implementation of marketing mix strategies covering product, price, place, and promotion, as well as to identify internal and external factors that influence income growth in the Es Coklat Berdua business in Bukittinggi City. This study used a qualitative approach with a case study design, involving five participants consisting of one business owner and four consumers selected through purposive sampling and snowball sampling techniques. Data were collected through observation, semi-structured interviews, and documentation, and were then analyzed using the interactive analysis model of Miles and Huberman combined with SWOT analysis through the IFAS and EFAS matrices. The results showed that the implementation of marketing strategies was not yet optimal, as indicated by limited product innovation, uncertainty regarding business location, and low utilization of digital marketing, although the business had strengths in product quality and competitive pricing. The SWOT analysis showed that the business position was in the Strength–Opportunity quadrant, indicating considerable development potential. The conclusion of this study affirms that the integration of marketing mix strategies, SWOT analysis, and sharia marketing principles needs to be implemented more comprehensively to increase business income. These findings contribute to the development of MSME marketing studies through an integrative approach and provide practical implications for business actors in designing more adaptive, competitive, and sustainable marketing strategies.